Analysis of multi-scale variability of incoming solar radiation on the Atlantic coast of Central Africa : in-situ measurements, satellite estimates and CMIP6 climate simulations. - (:unkn) unknown (My University, 2024)
Western Central Africa, home to the densest forests of the Congo Basin - the second largest tropical forest massif after Amazonia - is characterized by an equatorial climate with high temperatures, a bimodal rainfall pattern and, a long and cloudy dry season from June to September. Despite its ecological importance, the climate variability of this region has been less studied compared with other parts of the African continent, mainly because of the scarcity of in-situ observations.Recognizing these challenges posed by the lack of in-situ data, this study explores the climate variability in Western Central Africa through the lens of surface solar radiation, a key parameter for the functioning of tropical forests. In this context, this thesis aims to establish an initial climatology of surface solar radiation for the region, to document its variability, particularly during the cloudy dry season from June to September, and to assess the performance of satellite products, reanalyses and CMIP6 climate model simulations.In the first part, an evaluation of eight satellite products for estimating solar radiation (CERES-EBAF, CERES-SYN1deg, TPDC, CMSAF SARAH-2, CMSAF CLARA-A2, CAMS-JADE, WorldClim 2 and ERA5 reanalysis) reveals differences in the spatiotemporal fields. While successfully capturing mean annual solar radiation cycles, the products show regional variations, highlighting the impact of atmospheric parameters on the accurate estimation of solar radiation. In addition, all the products except WorldClim 2 agree that the Atlantic coast receives less solar radiation than the other regions of Central Africa. The performance of these products is also assessed against in-situ measurements based on four types of solar radiation diurnal cycle - Obscure, Obscure AM (morning), Obscure PM (afternoon) and Bright days. The products correctly represent the shape of these four types, but with a larger amplitude.The second part focuses on studying the interannual var
Keywords: African Research